Aceitação da cadeira obstétrica Nasce Já: um invento da enfermagem para humanização da assistência pré-natal - Franco, Eugênio Santana (2002)
The work tells about the acceptance of the obstetric chair be AIready Born for pregnant women as part of the actions for the nursing care in the prenatal assistence. It was aimed to verify the acceptance of the equipmentforthe customers and to reflect on the implications of this equipment during the gestacional period and in the nursing care. The exploratory descriptive, experimental with planned empiric interventions and quantitative approach study was destined to test the association among events, trying to verify if there is a causai relationship among them, and which results can demonstrate the acceptance of the equipment (obstetric chair be AIready Born) for the pregnant users. All the information was generated by experimentation and observation in laboratory during the prenatal assistance. The Study was developed in a Health Center of the municipal public net that offers prenatal assistance, located in the metropolitan area of Fortaleza - Ceará, where, to make the implantation of a new assistance model turned to the humanization of the prenatal assistance and the use of the obstetric chair be AIready Born possible, a room was built with appropriate physical space, equipped besides with audiovisual resources. Pregnant women with age were selected for inclusion in the study the between 15 and 40 years-old that didn’t refer to pathological antecedents, and that apparently the vaginal childbirth was not inadvisable for bringing on life risk to herself or to the fetus; the ones that didn’t have contraindication for accomplishment of physical exercises and that participated, at least, of eight sessions of exercises in the be is AIready Born chair during the gestacional period. The women’s average age admitted in the investigation was 23 years-old, the youngest age 15 years-old and the oldest 40, with standard deviation (dp) of 5,0, where 76 women (43,3%) belonged to the age group between 21 and 25 years-old.